Molecular characterization of hypoxia-inducible factor alpha isoforms reveals a pivotal role of HIF-3α in acute hypoxia adaptation of greenfin horse-faced filefish (Thamnaconus septentrionalis) - Mingyu Ma; Yi Bai; Zhewen Zhang; Xiaolei Su; Cong Liu; Wuhong Lv; Weiwei Liu; Kai Wang; Mingzhu Li; Qiangde Liu (Frontiers in Marine Science, 2026)
Introduction Hypoxia-inducible factor α (HIF-α) family members are key transcription factors mediating cellular responses to hypoxia. However, their specific roles in the greenfin horse-faced filefish, Thamnaconus septentrionalis , remain unclear. Methods The hypoxia sensitivity of T. septentrionalis was determined by the critical O 2 tension for loss of equilibrium (LOEcrit). Three TsHIF-α genes (TsHIF-1α, TsHIF-2α, and TsHIF-3α) were cloned and characterized through phylogenetic, structural and tissue expression analyses. Acute hypoxia responses were assessed in the liver, and dual-luciferase reporter assays were performed to examine transcriptional activation of the vegfa promoter. Results T. septentrionalis is highly sensitive to hypoxia, with a LOEcrit of 1.43 ± 0.2 mg/L. Phylogenetic and structural analyses confirmed that TsHIF-αs cluster into three canonical isoforms, with highly conserved basic helix-loop-helix (bHLH)-Per-Arnt-Sim (PAS) domains and divergent oxygen-dependent degradation domain (ODDD) regions, including fewer serine residues compared with homologs in other species. All three TsHIF-αs were broadly expressed, with higher levels in the head kidney and gill. Under acute hypoxia, TsHIF-3α exhibited rapid and sustained upregulation in the liver, preceding TsHIF-1α and closely paralleling the expression of the downstream target genes vegfa and ldha . Consistently, TsHIF-3α activates the vegfa promoter more efficiently than TsHIF-1α in a dose-dependent manner. Conclusion These results indicate that T. septentrionalis is a hypoxia-sensitive species that may rely on a TsHIF-3α-dominated regulatory mechanism to respond to acute hypoxia and enhance adaptive survival. This study advances understanding of HIF-α functional diversification in teleosts and provides a molecular framework for the genetic improvement of stress-resistant aquaculture species.